183 Intracranial Arachnoid Cysts and Hemorrhage. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Choi, Hoon; Madsen, Joseph R.; Scott, R. Michael; Warf, Benjamin C.; Cohen, Alan R.; Proctor, Mark R.; Huebenthal, Emma; Jernigan, Sarah C.; Goumnerova, Liliana
Abstract: INTRODUCTION: Intracranial arachnoid cysts are a relatively common finding on neuroimaging studies in the pediatric population (either incidental or symptomatic). Incidental lesions usually have a benign course and have been managed expectantly. On occasion, these cysts have presented with hemorrhage. We reviewed the clinical presentation, radiographic findings, management decisions, and surgical outcome of a single institution series of patients with intracranial arachnoid cysts who presented with hemorrhage. METHODS: Retrospective chart review was conducted on all patients at Boston Children's Hospital who were diagnosed with an intracranial arachnoid cyst with associated hemorrhage. Clinical presentation, physical examination, radiographic findings, surgical intervention, complications, and postoperative outcomes were examined. RESULTS: Between 1993 and 2014, 16 patients were diagnosed with an intracranial arachnoid cyst with subdural or intracyst hemorrhage at Boston Children's Hospital. Average age at presentation was 8 years and 81% were male. Of these patients, 62.5% had a history of recent head trauma. Two patients had a previous craniotomy for cyst fenestration. The most common presentation was headache, present in all but 1 patient (94%). Other common symptoms and findings included nausea and vomiting (62%), lethargy (25%), and papilledema (25%). Two patients had subtle weakness on presentation. Surgery was offered to all patients and performed in all but 1 patient, whose parents refused surgery for personal reasons. All patients who received surgery had resolution of the initial symptoms on subsequent follow-up. Two patients had a small, asymptomatic extra-axial fluid collection on follow-up imaging studies. Three patients (18.7%) subsequently required subdural-peritoneal shunt placement. One patient went on to require 3 shunt revisions. All patients who received a shunt had complete resolution of subdural hemorrhage. CONCLUSION: Intracranial arachnoid cysts can rarely present with hemorrhage. Surgery is safe and effective in these patients, and the possibility of a permanent shunt should be discussed with the patient and the family in advance.